Pseudo-Parallel Characteristic Jacobi Operators on Contact Metric 3 Manifolds - Wenjie Wang; Xinxin Dai (Journal of Mathematics)
We prove that the characteristic Jacobi operator on a contact metric three manifold is semiparallel if and only if it vanishes. We determine Lie groups of dimension three admitting left invariant contact metric structures such that the characteristic Jacobi operators are pseudoparallel.